Preparation of spinel LiMn2O4 cathode material from used zinc-carbon and lithium-ion batteries. Issue 5 (1st March 2022) - Sharifidarabad, Hadi; Zakeri, Alireza; Adeli, Mandana
Abstract: Due to the progressive shortage of primary resources and growing environmental concerns over industrial and household residues, proper management of electronic wastes is of great importance in addressing sustainability issues. Spent batteries are considered as important secondary sources of their constituting components. In this study, the co-recycling of used zinc-carbon and lithium-ion batteries was performed aiming at the recovery of their manganese and lithium contents as compounds which can be used as precursors for the synthesis of spinel LiMn2 O4 . Manganese was recovered in the form of amorphous, submicron, spherical nodules of MnO2 after acid leaching of zinc-carbon battery pastes. Lithium was obtained from nickel-manganese-cobalt (NMC) batteries as its monohydrate oxalate (C2 HLiO4 .H2 O) through selective leaching in oxalic acid followed by crystallization. Lithium carbonate was also prepared by subsequent calcination of the oxalate. The synthesis of LiMn2 O4 spinel cathode was investigated using the reclaimed Li- and Mn-containing compounds via solid-state synthesis method. The effect of such parameters as type of precursors (C2 HLiO4 .H2 O/Li2 CO3 with Mn2 O3 /MnO2 ), temperature (750, 800, and 850 °C), and time (8 and 10 h) on the synthesis of LiMn2 O4 was investigated. The products were characterized using X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. The crystallographic parameters from XRD analysis were used to predict the electrochemical behavior of the synthesized cathode materials. Based on these, the spinel powder synthesized at 850°C−10h from Li2 CO3 −Mn2 O3 starting mixture was determined as the cathode material with the best electrochemical properties among the synthesized samples. The galvanostatic charge/discharge evaluation within the voltage range of 2.5–4.3 V showed the specific capacity of the 850°C-10 h sample to be 127.87 mAhg −1 .